Management by processes and its incidence in the services of the district municipalities to 2016-province of Marañón - Remigio-Hilario, Alex M. (2019)
The aspects dealt with was the incidence of management by processes in the district Municipalities of the province of Marañón, the general objective of the investigation was to determine the incidence of the management by processes in the services of the district municipalities to 2016 - Province of Marañón , as well as, the determination of the incidence of the management by processes in the services of public cleaning, serenazgo service, administrative services, in the results and in the investment. The research method was descriptive according to the variable of interest, the type of research was observational, there was no intervention by the researcher, the data reflect the natural evolution of the events, beyond the researcher's will, according to the planning of the research. data, it was prospective data for the study were collected on the basis of research (primary). The main result is that the municipalities of the province of Marañón do not have defined processes in the services of public cleaning, citizen security, administrative, results and investment, the indicated processes are not met due to equipment deficiency and experience in the knowledge of the theory and an adequate implementation of them. The main conclusion of the research was process management is one of the best alternatives for local development and improvement of local services, however, the authorities attach little importance due to their ignorance and experience.